2011
DOI: 10.3384/ecp11057224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Factors that Affect The Lignin Content in The Reed Canarygrass (Phalaris arundinacea L.) in Latvia

Abstract: Abstract:In the production of granules from plants the cohesive substance lignin has a great importance, as it holds the granule together and does not allow it to disintegrate. The objective of this research was to evaluate the influencing factors of lignin content in reed canarygrass (Phalaris arundinacea L.) crop yield. In this research the varieties of reed canarygrass 'Marathon' and 'Bamse' were analysed for yields of first and second year. The lignin content of the samples was established by Classon's met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…What is interesting is the fact that in the first study year lignin amount in plants was the same regardless of the rate of mineral fertilizer. The findings of this study concur with reports by Poisa et al [54] whose work revealed a significant relationship between nitrogen fertilizer level and the amount of lignin in plants.…”
Section: Dose Of N Kg Hasupporting
confidence: 93%
“…What is interesting is the fact that in the first study year lignin amount in plants was the same regardless of the rate of mineral fertilizer. The findings of this study concur with reports by Poisa et al [54] whose work revealed a significant relationship between nitrogen fertilizer level and the amount of lignin in plants.…”
Section: Dose Of N Kg Hasupporting
confidence: 93%
“…Manure application might have improved lignin to cellulose ratio (L-C ratio) in roots and shoots of crops by augmenting N availability (Poisa et al 2011). Interestingly, L-C ratio of roots and shoots of both crops significantly influenced β-glucosidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, wood is the most important type of biomass in Latvia [2], however lately it has become common to cultivate different energetic plants and to use them in energy production. One of the most suitable plants for energy extraction and saving is reed canarygrass (Phalaris arundinacea L.) [3,4,5] which is widely studied in the world and is suitable for energy extraction in the conditions of Latvia [6,7,8]. Besides, for energy extraction it is possible to use the biomass of hemp (Cannabis sativa L) [9,10], flax (Linum usitissimum L.) [11,12], different grain and straw [13,14] and other plants.…”
Section: Introductionmentioning
confidence: 99%